Cartilaginous properties of nucleus pulposus cells seeded on poly(lactic-co-glycolic acid)-based scaffolds - Md Nazir, Noorhidayah; T. M., Tengku Nuramirah; Razak, Syahidah; Mohamad, Mohd Yusof; Abdul Rahman, Rozlin; Mohamad Syukri, Norhamiza; Ahmad Radzi, Muhammad Aa'zamuddin; Zulkifly, Ahmad Hafiz; Sha'ban, Munirah (Tissue Engineering and Regenerative Medicine Society of Malaysia, 2014)
Tissue engineering and regenerative medicine has the potential of improving the quality of life for many people. One particular area that presents an exciting challenge is the regeneration of intervertebral discs (IVD). To achieve this, it is necessary to identify suitable cells, biomaterial scaffolds and biologically active signalling factors for in vitro and in vivo IVD generation. This present study aimed to evaluate the cartilaginous properties of nucleus pulposus (NP) cells seeded on poly(lactic-co-glycolic acid) (PLGA) with or without fibrin scaffolds by measuring sulphated glycosaminoglycan (sGAG) content and collagen type II (COL-II) gene expression. The analyses were performed at week 1, 2, and 3 in vitro. The sGAG content was higher in the PLGA/Fibrin than in the PLGA only group. The expression of COL-II was only detected at week-2 culture in PLGA/Fibrin group. This study indicates that PLGA-based scaffolds may have the potential for intervertebral discs tissue engineering.